Economic Agenda for Nigeria - Nwankwo, Uchenna (Nigeria, Lagos : Centrist Productions, 1992)
The book describes the Nigerian economic environment, the Babangida approach to the economic issues and problems of the country.
includes index
includes bibliographies
occ 15/01/2019
Loans
Keywords: Economic policy; Economic history; Nigeria